Dealing with 'remote control': ritual healing and modernity in Western Kenya - Okwaro, Ferdinand (2013)
Like other former colonies in Africa, Kenya has a plural medical system consisting of traditional ritual healing as well as imported western biomedicine. Since the colonial period however, ritual healing has been subject to criticism and even persecution by the forces of modernity as represented by biomedical practitioners, the state and Christianity often acting in concert. This thesis examines why and how ritual healing persists in Kenya in spite of this criticism guided by the following three key questions: one, why ritual healing has persisted and continued to be part of the people’s health strategies even in the face of modernity; secondly how ritual healing adapts to the challenges posed by ‘modernity’ - challenges which include but are not limited to the hegemonic tendencies of biomedicine, emerging needs posed by modernity, the altered economic and social matrix of potential clients, economic necessities etc; and thirdly on the question of efficacy: how the efficacy of ritual healing can be adjudged. This dissertation is based on ethnography of ritual healers and their clients from Western Kenya conducted over a period of 15 months. The author initially interviewed several healers from Western Kenya before eventually selecting two of them for intense continuous observation of their ritual practices as well as interviewing and observing the outcome of their healing on their clients. Ethnographic notes, tape recorded interviews notes and video photography were employed for this study. With respect to the first question, this thesis observed that ritual healing persists in Western Kenya because it does what it purports to do, i,e. it heals. In its healing however ritual undergoes several alterations and adaptations including the incorporation of procedures that resemble those from biomedicine. On the question of adaptation this dissertation focuses more on practices rather than systems in view of the idiosyncratic nature of traditional healing in Africa as well as the desire to avoid the anthropological temptation to systematize a set of contingently related practices. Several ways in which ritual healers altered their rituals are examined and illustrations provided. The efficacy of ritual forms the last part of this dissertation. Here the author agrees with the argument by other scholars on ritual that the efficacy of any system of healing ought to be assessed according to their own set of standards and that although diverse forms of healing are recognized by their common concern to alleviate suffering, prolong life and reduce disability, their effectiveness could be judged against their ability to achieve goals that vary widely across different settings and traditions. By means of selected case studies, this dissertation shows that the efficacy of ritual was based on the fact that healers provided comprehensive and acceptable narratives that captured the clients’ affliction and proposed remedial actions that led to their resolution. The expectation that ritual healing was something traditional that would automatically disappear with modernisation does not fit with actual developments in Western Kenya today and in Africa as a whole. The persistence of ritual is however not a rejection of the project of modernity. Rather it is the rejection of the dichotomies in the modernist paradigm that propose that tradition and modernity do not belong together. Contemporary ritual healing practices not only call for a reconsideration of the teleology of the project of modernity but also for the possibility of modernities being multiple, where a society can be modern while still retaining the practices and institutions, such as rituals healing, that according to the old modernisation paradigm ought to be effaced for the project of modernity to be complete.
Keywords: Hochschulschrift; Heilung; Ritual; Kenia